Fabrication of Naturally Derived Double-Network Hydrogels With a Sustained Aspirin Release System for Facilitating Bone Regeneration - Zhu, Wenfeng; Chen, Rui; Wang, Weiheng; Liu, Yi; Shi, Changgui; Tang, Songjun; Tang, Guoke (Frontiers in Chemistry, 2022)
Continuous efforts on pursuit of effective drug delivery systems for engineering hydrogel scaffolds is considered a promising strategy for the bone-related diseases. Here, we developed a kind of acetylsalicylic acid (aspirin, ASA)–based double-network (DN) hydrogel containing the positively charged natural chitosan (CS) and methacrylated gelatin (GelMA) polymers. Combination of physical chain-entanglement, electrostatic interactions, and a chemically cross-linked methacrylated gelatin (GelMA) network led to the formation of a DN hydrogel, which had a suitable porous structure and favorable mechanical properties. After in situ encapsulation of aspirin agents, the resulting hydrogels were investigated as culturing matrices for adipose tissue–derived stromal cells (ADSCs) to evaluate their excellent biocompatibility and biological capacities on modulation of cell proliferation and differentiation. We further found that the long-term sustained ASA in the DN hydrogels could contribute to the anti-inflammation and osteoinductive properties, demonstrating a new strategy for bone tissue regeneration.